Then and Now: Formative Experiences and Generational Perspectives among Flemish GBTQ Baby Boomers - Alexander Dhoest (Journal of Men's Health, 2022)
Background: This paper proposes a generational approach to better understand the specific position and perspectives of older GBTQ (Gay, Bisexual, Transgender and Queer) men. Generational theory and empirical research demonstrate that experiences and social contexts in adolescence and early adulthood are formative for sexual identity formation while also informing perspectives later in life. Methods: The paper discusses the findings of a qualitative project based on in-depth interviews with sixteen Flemish men belonging to the so-called “Baby Boomer” generation, i.e., born between 1945 and 1964. They came of age before “gay liberation”, exploring and establishing their sexual identities in a period of social invisibility. Results: First, the analysis focuses on the past, in particular the period of sexual exploration and identity formation, reporting findings on formative, often difficult experiences such as the first realization of same-sex attraction, first sexual explorations, coming out, first contact with other LGBTQ (Lesbian, Gay, Bisexual, Transgender and Queer) individuals, participation in the LGBTQ scene and associations, and HIV/AIDS. Then, the focus shifts to the present, to discuss the progress the participants observe but also the problems they (still) experience, including the way they perceive intergenerational differences. Conclusions: Older GBTQ men came of age in a radically different context, struggling to embrace their sexuality, which also informs their current position in LGBTQ culture. These insights are relevant for LGBTQ associations, policy makers and (mental) health practitioners, who could do more to address the specific position and needs of this older demographic.